ANALISIS IMPLEMENTASI KURIKULUM MANDIRI DALAM KEGIATAN BELAJAR MENGAJAR DI MTS INSAN MADANI - Sundarwati, Desi; Darmawati, Lusi Endang; Dassucik (Yayasan Amanah Nur Aman, 2025)
This article is written to discuss the implementation of the Merdeka Curriculum at MTs. Insan Madani. A curriculum itself is a plan or regulation that contains the objectives, content, learning materials, and teaching methods used as guidelines in the teaching and learning process. The curriculum can also be defined as a set or system of plans and arrangements regarding learning materials that can be used as a guide in conducting teaching and learning activities. In essence, the curriculum can also be referred to as a learning plan. This research is qualitative in nature. The method used is a descriptive approach with data collection conducted through in-depth interviews and observation. The subjects of this study are students at the MTs. Insan Madani education unit, located in Gebang Village, Jatibanteng District, Situbondo Regency. The data collection technique used is qualitative descriptive data, collected in the form of words or images. The results of this study reveal that the implementation of the Merdeka Curriculum at MTs. Insan Madani is influenced by several factors, namely the natural resources of the institution itself and the transitional process from the previous curriculum. As a result, there are still some teachers who do not fully understand how to implement the Merdeka Curriculum properly.